Understanding the dialysis access steal syndrome. A review of the etiologies, diagnosis, prevention and treatment strategies - Malik, J; Tuka, V; Kasalova, Z; Chytilova, E; Slavikova, M; Clagett, P; Davidson, I; Dolmatch, B; Nichols, D; Gallieni, M (The journal of vascular access, 2008)
Distal hypoperfusion ischemic syndrome (DHIS), commonly referred to as hand ischemia or 'steal' after dialysis access placement, occurs in 5-10% of cases when the brachial artery is used, or 10 times that of wrist arteriovenous fistulas (AVFs) using the radial artery. It is typically seen in elderly women with diabetes, and may carry severe morbidity including tissue or limb loss if not recognized and treated. Three distinct etiologies include (1) blood flow restriction to the hand from arterial occlusive disease either proximal or distal to the AV access anastomosis, (2) excess blood flow through the AV fistula conduit (true steal), and (3) lack of vascular (arterial) adaptation or collateral flow reserve (ie atherosclerosis) to the increased flow demand from the AV conduit. These three causes of steal may occur alone or in concert. The diagnosis of steal is based on an accurate history and physical examination and confirmed with tests including an arteriogram, duplex Doppler ultrasound (DDU) evaluation with finger pressures and waveform analysis. Treatment of steal includes observation of developing symptoms in mild cases. Balloon angioplasty is the appropriate intervention for an arterial stenosis. At least three distinct surgical corrective procedures exist to counteract the pathophysiology of steal. The ultimate treatment strategy depends on severity of symptoms, the extent of patient co-morbidity, and the local dialysis access technical team support and skills available.
Keywords: Upper Extremity; Ultrasonography, Doppler, Duplex; rizikové faktory; Renal Dialysis; Ischemia; dialýza ledvin; syndrom; Kidney Failure, Chronic; horní končetina; Humans; chronické selhání ledvin; Arteriovenous Shunt, Surgical; Risk Factors; duplexní dopplerovská ultrasonografie; arteriovenózní zkrat; Syndrome; lidé; ischemie